The relationship between pre-service teachers' self efficacy and their internet self-efficacy - Gurol, Aysun; Akti, Seda (Elsevier Science Bv, 2010)
The present study seeks to investigate the relationship between pre-service teachers' self efficacy and their internet self-efficacy beliefs. It also seeks to determine how much pre-service teachers' self efficacy contributes to the prediction of their sense of internet self-efficacy. The study reported in this paper was conducted to examine the relationship between pre-service teachers' internet self-efficacy and their self-efficacy in Faculty of Education. To this end, 248 pre-service teachers were selected from Faculty of Education in Firat University, in Turkey. The participants were asked to complete the pre-service teachers' Sense of Self-Efficacy Scale and the 'Pre-service Teachers' Internet Self-Efficacy Questionnaire. Data analysis and statistical calculations revealed that there is a significant relationship between pre-service teachers' internet self-efficacy and their self-efficacy. To investigate of Internet Self-Efficacy might have more predictive power in predicting pre-service teacher's self-efficacy, regression analysis was run. The conclusions and implications of the research were discussed with reference to the earlier findings. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Pre-service teacher; self-efficacy; teachers' self-efficacy; pre-service teachers' internet self-efficacy